PENGARUH CUSTOMER ENGAGEMENT DAN VIRAL MARKETING TERHADAP BRAND AWARENESS PADA PRODUK HANDPHONE MERK VIVO (Studi Kasus Pada Konsumen Vivo Bintang Cell Simpang Tabuik Pariaman) - Asrul Asrul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The purpose of this study is to examine simultaneously and partially the influence of customer engagement and viral marketing on brand awareness on vivo brand mobile products in the city of Pariaman. Based on the results of this study it is hoped that this research can provide consideration in determining customer engagement and viral marketing policies so that it can increase brand awareness. Based on the results of the study note that the influence of customer engagement on brand awareness t value was calculated at 6.277 with a significance level of 0.000